1989
DOI: 10.1111/j.2042-7158.1989.tb06493.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid production of ulcerative disease of the colon in newly-weaned guinea-pigs by degraded carrageenan

Abstract: In a dose-response study, degraded carrageenan (Eucheuma spinosum) was supplied in the drinking fluid at 1.2 and 3% concentrations over two weeks to young adult guinea-pigs. Ulceration of the large bowel was produced in 100% of animals, the severity and extent of damage probably being dose-related. In a time-course study, 3% degraded carrageenan solution supplied to newly-weaned guinea-pigs produced in 100% of animals ulceration in the caecum by four days and in the ascending colon by seven days. The onset of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 7 publications
2
24
0
Order By: Relevance
“…The amounts of poligeenan consumed by animals in the Sentinel and Compromised groups were essentially equal: 4.1 and 4.0 g/kg/day, respectively. Animals in these groups exhibited several findings consistent with published observations of the effect of poligeenan on the GI tract (Grasso et al, 1973;Anver and Cohen, 1976;van der Waaij et al, 1974;Marcus et al, 1988). Diarrhea or soft stools, anogenital staining, and the presence of blood in the refuse pan were observed among animals in both groups.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The amounts of poligeenan consumed by animals in the Sentinel and Compromised groups were essentially equal: 4.1 and 4.0 g/kg/day, respectively. Animals in these groups exhibited several findings consistent with published observations of the effect of poligeenan on the GI tract (Grasso et al, 1973;Anver and Cohen, 1976;van der Waaij et al, 1974;Marcus et al, 1988). Diarrhea or soft stools, anogenital staining, and the presence of blood in the refuse pan were observed among animals in both groups.…”
Section: Resultssupporting
confidence: 87%
“…In this study, feeding poligeenan for 5 weeks produced damage in the GI tract of the guinea pigs similar to that reported by others (Grasso et al, 1973;Anver and Cohen, 1976;van der Waaij et al, 1974;Marcus et al, 1988). Endoscopic examination of the lower GI tracts of the Sentinel animals (poligeenan-fed animals killed 1 day before the animals in the other groups were dosed with radiolabeled olestra) confirmed that the GI mucosa was damaged extensively.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These activities largely depend on the molecular weight of the polymer (34) and the amount of sulfations along the polysaccharide chain, both factors which are modulated with specific microbial CAZymes and sulfatases (29). Indeed, health implications and concerns have been associated with the low-molecular-weight degradation products of carrageenan, which elicited ulcerative colitis in animal models (11,(35)(36)(37). Our screening for red algal galactan degrading gut microbes revealed B. thetaiotaomicron VPI-3731, which presented strong growth on carrageenan and must therefore contain one or more carrageenases.…”
Section: Discussionmentioning
confidence: 99%
“…Some sulfated polysaccharides, such as degraded carrageenan [1][2][3] , dextran sulfate sodium 4,5 , and sulfated amylopectin 6,7 can produce ulcerative disease of the colon in experimental animals when added to their drinking water. Topical application of trinitrobenzen sulfonic acid 8 or acetic acid [8][9][10] can also produce ulcerative colitis.…”
Section: Introductionmentioning
confidence: 99%